Comparisons of Competitiveness in U.S. and Swedish Manufacturing - Bo Carlsson (The Research Institute of Industrial Economics (IUI), 1989)
Over the course of the last 10 or 15 years there appears to be taking place a fundamental shift in the 'industrial paradigm' governing the nature of competition in advanced industrial markets. Among the characteristics of this shift are a transition from mass production to flexible manufacturing technologies, reduced time for development of new products, shorter product life cycles, increased product diversity, increasing expenditures on industrial R&D, shrinking firm size ('deglomeration'), specialization on 'niches' or 'core business areas', and more intense global competition even in products that previously seemed exempt from such pressures. The object of this paper is to bring these themes together by examining the development of the competitive position in world markets of the United States and Sweden, two countries which are apparently pursuing very different strategies in dealing with the new challenges. The first part of the paper examines the international trade performance of the two countries with emphasis on different patterns of trade with respect to goods of varying research and development intensity. A simple model for analyzing the differences in performance is suggested in the second section. The third section draws together fragments of empirical evidence in support of the hypothesis.
Keywords: F10; L23; L25; O32; O57; 330; Competition in industrial markets; production methods; R&D; specialisation; trade performance